Behavioral and social interventions to promote optimal HIV prevention and care continua outcomes in the United States. Issue 2 (March 2022) - Gamarel, Kristi E.; King, Wesley M.; Operario, Don
Abstract : Purpose of review: This review reports on trends in behavioral and social intervention research in the United States published over the past year (2020–2021) investigating HIV prevention and care outcomes, organized by the level of intervention focus – individual, dyadic, and organizational. Recent findings: Researchers have continued to develop and evaluate behavioral and social interventions to reduce HIV acquisition risk and disease progression. With few exceptions, social and behavioral interventions have primarily focused on individuals as the unit of behavior change. Interventions operating at the individual-, dyadic-, and organizational-level have made strides to reduce HIV transmission risk and disease progressing by addressing mental health, substance use, stigma, peer and romantic relationships, and, to some extent, structural vulnerabilities. Summary: Social and behavioral interventions continue to be critical in addressing HIV inequities in the United States. An important gap in the literature is the need for multilevel interventions designed and implemented within existing community-based organizations and local healthcare settings. We call on researchers to continue to attend to the structural, environmental, and economic vulnerabilities that shape HIV inequities in the development of multilevel approaches necessary to realize the full potential of existing and emerging HIV prevention and care strategies.